2012
DOI: 10.4236/ojpm.2012.22026
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome occurrence in university students from México City: The binomium HDL/waist circumference is the major prevalence factor

Abstract: Objective: Metabolic Syndrome (MetS) is the leading cause to develop type 2 diabetes worldwide. We examined associations of MetS components early in life, and their use as risk factors of acquiring MetS. Method: We used an international definition of MetS. Subjects were categorized into "Healthy"/"Not Healthy", altered parameters are low HDL-cholesterol, large waist circumference (WC), hypertriacylglycerolemia, hypertension, and hyperglycemia, in 32 combinations (2^5) with two values (altered/not altered). Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
5
0
2
Order By: Relevance
“…Estos hallazgos son consistentes con los resultados obtenidos en un estudio realizado en jóvenes universitarios de la ciudad de México, en el que se observó que el binomio HDL/ circunferencia de cintura fue el principal factor relacionado con el síndrome metabólico en jóvenes asintomáticos, seguido de la hipertrigliceridemia, hipertensión e hiperglicemia (8). Las diferencias en la composición corporal y en el metabolismo de lípi-dos entre hombres y mujeres se pueden atribuir a la acción de las hormonas esteroideas que son responsables del dimorfismo sexual, que se desarrolla primariamente durante la pubertad y que se mantiene durante el resto de la vida (9,10).…”
Section: Discussionunclassified
“…Estos hallazgos son consistentes con los resultados obtenidos en un estudio realizado en jóvenes universitarios de la ciudad de México, en el que se observó que el binomio HDL/ circunferencia de cintura fue el principal factor relacionado con el síndrome metabólico en jóvenes asintomáticos, seguido de la hipertrigliceridemia, hipertensión e hiperglicemia (8). Las diferencias en la composición corporal y en el metabolismo de lípi-dos entre hombres y mujeres se pueden atribuir a la acción de las hormonas esteroideas que son responsables del dimorfismo sexual, que se desarrolla primariamente durante la pubertad y que se mantiene durante el resto de la vida (9,10).…”
Section: Discussionunclassified
“…Total prevalence of AOb in this sample was lower compared with that found in a nationwide Mexican young adults 20-29 y (41.1% vs. 53.3%, respectively) (12), which is alarming since these elements are closely related to the MetS. Assuming the MetS as a multifactorial process, it is a progress between "healthy" and "not healthy" status, early events of that process might predict progression to future chronic disease (17). Screening and identifying young adults, especially men, with conditions such as AOb, dyslipidaemia and the MetS are crucial steps in establishing effective educational and intervention strategies to reduce the incidence and burden of chronic diseases.…”
Section: Discussionmentioning
confidence: 62%
“…According to the results of this study, low HDL-C was the most frequent, followed by AOb. In 2012, our research group suggested that the binomium HDL/WC is the main prevalence factor and the main predictor of MetS occurrence, since low HDL-C is very frequent in this population (17). However, to increase the effectiveness of these interventions and as a goal of this report, we consider that is more important to know the degree of association of each of these elements on its development.…”
Section: Discussionmentioning
confidence: 93%
“…In contrast, HOMA needs the measurement of both fasting plasma insulin and glucose to make an estimation of IR in steady state conditions [4]. On the other hand, it has recently been found that Mexican population has genetic factors that make them vulnerable to MetS related impairments [5], which may underlie the high prevalence of MetS in the young adult population [6,7]. Hence, to know the risk of young Mexicans to develop MetS may help prevent, in a more efficient way, the chronic diseases that follow after MetS.…”
Section: Introductionmentioning
confidence: 99%
“…Since pancreatic β cells produce insulin to abate high glucose levels, in early stages of MetS, i.e., the Mexican young population, it is more probable to detect altered values in insulin than in glucose, and hence a tool to detect IR with high sensitivity became very relevant. Even though the high prevalence of MetS among Mexicans [8], and particularly among the young population [6,7], to date no studies have been reported to establish cut-off points for insulin neither for insulin resistance model assessment (HOMA-IR) [3] in Mexican young population, thus a cut-off point to detect IR in young Mexicans with high sensitivity is needed. The objective of this study was to establish, and then propose cut-off points for normal values of insulin and HOMA-IR in young Mexicans.…”
Section: Introductionmentioning
confidence: 99%